Protective effects of nanostructures of hydrated C60 fullerene on reproductive function in streptozotocin-diabetic male rats - Bal, R; Türk, G; Tuzcu, M; Yılmaz, Ö; Özercan, İ; Kuloğlu, T; Gür, S; Nedzvetsky, Vs; Tykhomyrov, Aa; Andrievsky, Gv; Baydaş, G; Naziroğlu, M (My University, 2011)
Diabetes mellitus is a well-recognized cause of male sexual dysfunction and impairments of male fertility. Streptozotocin (STZ) is used for medical treatment of neoplastic islet -cells of pancreas and producing of animal model of diabetes mellitus type 1 that is characterized by suppression of reproductive activity due to the hyperglycaemia-induced oxidative stress and histopathological alterations in testes. Seeking for the agents that could alleviate diabetes-induced damage to reproductive system is yet the important area of inquiry. The present study was designed to evaluate whether hydrated C60 fullerene (C60HyFn), which is known to be powerful bioantioxidant, eliminate testicular dysfunction induced by STZ-diabetes in rats. Wistar strain male albino rats were divided into four groups of six animals each: (1) control group, (2) C60HyFn-treated nondiabetic group, (3) STZ-diabetic group and (4) C60HyFn-treated diabetic group. Once hyperglycaemia was induced by STZ, rats in the second and fourth groups were treated with C60HyFn (in the form of drinking water) at the dose of 4 g/kg daily for 5 weeks. In diabetic rats, relative weights of right cauda epididymis, seminal vesicles, prostate, sperm motility and epididymal sperm concentration were significantly less than those of control group, but which were restored in the fourth group treated with C60HyFn (p < 0.001). In hematoxylin and eosin staining, marked histopathological changes including degeneration, desquamation, disorganisation and reduction in germinal cells, interstitial oedema and congestion were evident in the testis of diabetic rats, but C60HyFn treatment resulted in recovery of histopathological changes and an increase in Johnsen’s testicular score significantly (p < 0.001). C60HyFn treatment restores the increased apoptosis induced by STZ-diabetes. In diabetic rats, levels of serum testosterone, testicular reduced glutathione (GSH) and alpha-tocopherol were significantly reduced and testicular lipid peroxidation level was increased (p < 0.001). Nevertheless, treatment of diabetic rats with C60HyFn resulted in significant corrective effects on these parameters towards the control levels. C60HyFn, applied alone, did not exert any toxic effects in testicular tissues. Furthermore, C60HyFn treatment in diabetic and nondiabetic rats resulted in considerable elevations of some important polyunsaturated fatty acids. In conclusion, we have presented for the first time substantial evidence that administration of C60HyFn significantly reduces diabetes-induced oxidative stress and associated complications such as testicular dysfunction and spermatogenic disruption
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Streptozotocin Diabetes mellitus Hydrated C60 fullerene Testis Oxidative stress Apoptosis Sperm characteristics Fatty acid composition